The Role of Socio-Cultural Competence in Teaching Foreign Languaegs - Feruza Shakirovna Kattayeva (International Journal on Integrated Education, 2022)
In the present study author examines the problem of development ofsocio-cultural competence in teaching foreign languages. Sociocultural competence is most often understood as: "the ability of a person to communicate with representatives of different age and social groups", conscious expression of a personality manifested inher beliefs, motives, attitudes on a certain behavior, in the formation of personal qualities that contribute to constructive interaction, the presence of a set of skills and behavioral skills in a certain society under appropriate circumstances.